Introducing the Massachusetts CSI Nursing Delirium Collaborative. Issue 11 (November 2016) - DiLibero, Justin; Edwards, Erica; Hanson, Dave
Abstract : The final installment of our Clinical Scene Investigator series describes how several facilities collaborated to improve patient care.